Fagonia: A potential medicinal desert plant - Puri, Dinesh; Bhandari, Anil (Journal of Nepal Pharmaceutical Association, 2015)
Desert plants are unique adaptation from environmental conditions. Fagonia is a genus of plant in the family zygophyllaceae with about 20 species around Mediterranean to India, S. Africa, California, Chili. The local name of fagonia is dhamasa. They are traditionally well known for the treatment of hemorrhoids, inflammation, sores, leprosy, open wounds and fever in the form of internal and external conventional formulation. When the powder that is made up of the whole plant of F. schweinfurthii is dusted on boils and skin eruptions, it causes healing, when the whole plant is boiled in water, its bath is useful for allergies and other skin diseases and decoction is given orally as blood purifier. The other species like Fagonia bruguieri its aqueous extract is claimed for anti-allergy. Methanolic extract of Fagonia cretica is claimed for good antimicrobial potential and it exhibited strong free radical scavenging properties against reactive oxygen and nitrogen species. The other effects of Fagonia species include anti-inflammatory, analgesic, antipyretic and thrombolytic activities are observed. Many chemical constituent’s, such as triterpenoids, saponins, flavonoid glycosides, etc., have already been reported in different Fagonia spp. DOI: http://dx.doi.org/10.3126/jnpa.v27i1.12147 Journal of Nepal Pharmaceutical Association 2014 Vol.XXVII: 28-33